Optimalisasi Kedisiplinan Belajar Siswa melalui Sistem Star Rewards dalam Pembelajaran Kooperatif di SDN 1 Bugel - Syifa Fajriyal Ulya; Salsabila Bilqis; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Good study habits are an important factor in achieving success in elementary school learning. However, based on observations in class 3 of SDN 1 Bugel, it was found that students still show less disciplined behavior during the learning process, especially during group activities, such as talking without permission, not paying attention, and not following classroom rules. This study aims to improve students' study discipline in grade 3 of SDN 1 Bugel by using the Star Rewards system within the cooperative learning model called Numbered Heads Together (NHT). This study uses the Classroom Action Research (PTK) approach with a two-cycle design following the Kemmis and McTaggart model. The research subject is 17 third-grade students from SDN 1 Bugel. Data collection was done through observation, questionnaires, documentation, field notes, and interviews. Data analysis was done using both quantitative and qualitative descriptive techniques. The research results show that using the Star Rewards system in cooperative learning type NHT has significantly improved students' discipline in studying. The average score on the discipline questionnaire increased from 69.5 in cycle I to 85.5 in cycle II, showing an increase of 16.03 points. The minimum score for students has gone up from 50 to 75, showing that all students have improved in terms of discipline. Giving positive reinforcement through stars has been proven to motivate students to be more disciplined, focused, and responsible during learning. This finding suggests that combining the NHT model with the Star Rewards system can be an effective strategy for helping build discipline in elementary school students.